ANALYSIS OF STUDENTS’ UNDERSTANDING IN USING GUAI (具合), CHOUSHI (調子 ), AND TSUGOU (都合) IN THE JAPANESE SYNONYM - Sri Aju Indrowaty; Nurul Faizah; Dhea Yhustien Wahyuning; Oktavia Hasna (Jurnal Kata, 2023)
The Japanese language consists of many words that have almost similar meanings but contain different nuances and uses. So many intermediate-level Japanese students do not understand the difference between words that have the same meaning (synonyms). One of the synonyms with the most errors is the difference in the use of the nouns guai, choushi, and tsugou. This study aims to describe students' understanding of the use of guai, choushi, and tsugou and the differences and relationships among the three nouns. This study used a descriptive-qualitative approach. The data used were test results and questionnaires which distributed to intermediate-level Japanese learners. The techniques of analysis data were based on Miles and Huberman to describe students' understanding, as well as permutation and replacement techniques to describe the differences between guai, choushi, and tsugou. The results show that students have a better understanding of the meaning of tsugou than choushi and guai in the context of sentences. Guai and choushi have interchangeable meaning relationships, while tsugou can be replaced with guai to express conditions related to compatibility. Guai and choushi can be used to indicate bodily conditions and moods, but choushi only can be used to indicate conditions visible to the senses.